A new species of Larsia Fittkau, 1962 (Diptera: Chironomidae: Tanypodinae) from phytotelmata of Aechmea distichantha Lemaire, 1853 (Bromeliaceae) in Argentina - Siri, Augusto (2015)
A new species of Larsia Fittkau, 1962 is described and figured as adults and immatures based on larvae collected from phytotelmata of the bromeliad Aechmea distichantha Lem. in northeastern Argentina, and reared to the adult stage. The pupa bears unusual thoracic horns for the genus, which distinguish this new species from other Larsia species.